2015
DOI: 10.1016/j.bbrep.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Human retinal pigment epithelial cell proliferation by the combined stimulation of hydroquinone and advanced glycation end-products via up-regulation of VEGF gene

Abstract: Although recent research showed that advanced glycation endproduct (AGE) and hydroquinone (HQ) are related to the pathogenesis of age-related macular degeneration (AMD), the mechanism how AGE and HQ induce or accelerate AMD remains elusive. In the present study, we examined the effects of AGE and HQ on changes of human retinal pigment epithelial (RPE) cell numbers and found that the viable cell numbers were markedly reduced by HQ by apoptosis and that AGE prevented the decreases of HQ-treated cell numbers by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 58 publications
1
67
0
1
Order By: Relevance
“…Cigarette smoke destroys the macular area by increasing oxidative stress and suppressing the antioxidative system [9]. Hydroquinone is one component in the cigarette smoke, which is known to induce oxidative stress and apoptosis, and compromise cell viability concentration-dependently in RPE cells [16,21,27,43]. Our results are in line with the observation that hydroquinone-induced cytotoxicity is concentration-dependent and increases oxidative stress in RPE cells [16][17][18].…”
Section: Discussionsupporting
confidence: 89%
“…Cigarette smoke destroys the macular area by increasing oxidative stress and suppressing the antioxidative system [9]. Hydroquinone is one component in the cigarette smoke, which is known to induce oxidative stress and apoptosis, and compromise cell viability concentration-dependently in RPE cells [16,21,27,43]. Our results are in line with the observation that hydroquinone-induced cytotoxicity is concentration-dependent and increases oxidative stress in RPE cells [16][17][18].…”
Section: Discussionsupporting
confidence: 89%
“…Total RNA was isolated using RNeasy Protect ® Cell Mini kit (Qiagen, Hiden, Germany) from FaDu cells. cDNA was reverse transcribed from 0.5-2 µg samples of total RNA using High-Capacity cDNA Reverse Transcription kit (Applied biosystems, Foster City, CA, uSA) as described (44,45,(47)(48)(49)(50)(51). cDNA was subjected to PCR with the following primers, synthesized and prepared by Nihon Gene Research Laboratories, Inc. (NGRL; Sendai, japan): β-actin (NM_001101) sense, 5'-GCGAGAAGATGACCCAGA-3' and antisense, 5'-CAGAGGCGTACAGGGATA-3'; REG Ⅲ (Ab161037) sense 5'-GAATATTCTCCCCAAACTG-3' and antisense, 5'-GAGAAAAGCCTGAAATGAAG-3'.…”
Section: Methodsmentioning
confidence: 99%
“…However, the molecular mechanism by which statins reduce the risk of AMD remains unclear. Recently, we reported that the combination of hydroquinone (HQ; benzene-1,4-diol) and advanced glycation endproducts (AGE) increased the expression of VEGF-A in RPE cells and that VEGF induced RPE cell proliferation as an autocrine growth factor [8] . In this study, we examined the effects of statins on the expression of VEGF-A and on receptor for AGE ( RAGE ) using the HQ + AGE-induced in vitro AMD model.…”
Section: Introductionmentioning
confidence: 99%